Does Nilaparvata lugens gain tolerance to rice resistance genes through conspecifics at shared feeding sites? - Ferrater, Jedeliza B.; Horgan, Finbarr G. (Wiley, 2016)
This study examines the possibility of horizontal and vertical transmission of virulence (the ability to tolerate a given resistant plant or resistance gene) between individuals from brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), populations with distinct feeding abilities when their populations share the same feeding sites (virulence acquisition hypothesis). We created optimal conditions for intraspecific interactions on the same rice, Oryza sativa L. (Poaceae), plants between planthoppers from populations with different feeding histories: an ‘avirulent’ population that was continually reared on a susceptible variety, and a ‘virulent’ population that had been selected over several generations on the resistant variety IR62, that possesses the Bph3 gene. We noted that planthoppers attained highest weights on rice plants that had previously been attacked by conspecifics from the IR62‐selected population. We also tested the ability of planthoppers to feed on IR62 and the susceptible cv. Taichung Native 1 (TN1) after interacting with individuals from the IR62‐selected population on a tolerant rice cultivar (Triveni). Feeding by avirulent planthoppers on both IR62 and TN1 improved after feeding on the same rice plants with virulent planthoppers. Furthermore, the effects were carried over to planthopper progenies. Our preliminary results indicate that feeding by mixed populations that include individuals adapted to feed on resistant varieties potentially accelerates adaptation by N. lugens to rice resistance.